2007
DOI: 10.1007/s11136-007-9233-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between infant feeding pattern and mother’s quality of life in Taiwan

Abstract: Compared to the other mothers, mothers who breastfed for six moths or longer had better HRQOL. However, the limitation that this study was cross-sectional in design should be considered and further studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 51 publications
(55 reference statements)
1
37
1
Order By: Relevance
“…161 Two measured incident type 2 diabetes based on an oral glucose tolerance test; 159, 160, 163 one of these also searched an electronic medical record for diagnoses made on other criteria (e.g., hemoglobin A1c). 160,163 The third relied on administrative databases to determine incident diabetes (using hospital and outpatient diagnosis codes). 161 Ascertainment of breastfeeding exposure and length of followup differed across studies.…”
Section: Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…161 Two measured incident type 2 diabetes based on an oral glucose tolerance test; 159, 160, 163 one of these also searched an electronic medical record for diagnoses made on other criteria (e.g., hemoglobin A1c). 160,163 The third relied on administrative databases to determine incident diabetes (using hospital and outpatient diagnosis codes). 161 Ascertainment of breastfeeding exposure and length of followup differed across studies.…”
Section: Characteristicsmentioning
confidence: 99%
“…One study measured breastfeeding duration and exclusivity prospectively (via feeding diaries, telephone interviews, in-person exams, and monthly mailed questionnaires) and categorized breastfeeding exposure based on interviews at 6 to 9 weeks postpartum (exclusive formula, mostly formula, mostly lactation, and exclusive lactation); incident diabetes was measured at 2 years. 160 The two other studies measured breastfeeding status at hospital discharge and followed women over a longer time frame; one followed women for 7 years postpartum 159 and the other followed women for up to 24 years. 161 Three studies reported on incident diabetes among women without known gestational diabetes.…”
Section: Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations